PERANCANGAN APLIKASI PEMBELAJARAN GRAMMAR DAN LISTENING BAHASA INGGRIS - toni, toni; simanjuntak, pastima (Computer Science and Industrial Engineering, 2022)
ABSTRACT English is the official language in various countries in Europe, America, and Africa, therefore official English is considered as the first international language in the world. This is the main reason English is a compulsory subject in schools. Based on an article published by the UKI English Education Department, it states that there are several factors that hinder students in learning English including, namely the lack of student motivation and students rarely practice English outside of class hours and the English language material available at school is of course limited due to lack of Learning hours at school are a maximum of only four hours a week. The purpose of this study is to design an application for learning English grammar and vocabulary on the Android platform and the method used is the Rapid Application Development method. This application is designed using Smart Apps Creator, Microsoft PowerPoint, and Adobe Photoshop. With the creation of an application design for learning English grammar and listening, it is hoped that it can increase the knowledge and insight of students or users of this application and correct grammatical errors in English. Keywords: English; Smart App Creator; Android Platform;